Randall Park Architectural and Historical Survey - Herold, Kelly; Borowski, Katie (My University, 2012)
The City of Eau Claire's comprehensive planning documents show that their goal for historic preservation is to "Identify, protect, and preserve Eau Claire's resources, which reflect distinctive elements of the City's cultural, social, economic, political, historical, and architectural heritage in order to enhance the quality of life and foster pride and knowledge about Eau Claire's past." This study provided an opportunity to learn research methods while providing a public service to the City of Eau Claire, as well as the Wisconsin State Historic Preservation Office.
Color poster with text, images, and maps.
Keywords: Randall Park (Eau Claire, Wis.)--History; Architecture--Wisconsin--Eau Claire; Posters